Using Computer Processing Interpretation (CPI) Technique to Evaluate Mishrif Formation in Garraf Oil Field, Southern Iraq - Al-Yasi , Ameen I.; A. Jaed , Mustafa (Iraqi Journal of Science, 2022)
The aim of this study is to determine and evaluate the units and subunits of Mishrif Formation in Garraf oil field 85 km north of Nasiriyah city depending mainly on the geophysical well logging data and other amiable geological information. The sets of the geophysical well logs data acquired from GA-4, GA- AIP, GA- B8P, GA-3 and GA-5 wells of Garraf oil field are used to determine the petrophysical and lithological properties for each zone in Mishrif Formation to locate, define and evaluate hydrocarbon production from each zone in the reservoir which is also known as formation evaluation. The digitization was done by using Didger software and the interpretations were made using Interactive Petrophysics Program v 3.5 and Petrel software. It is found that middle and Lower parts of Mishrif Formation include several reservoir units (M 1.2, L 1, L 1.2, L 2, L 2.2, L 2.3 and L 2.4) that have been sealed by two cap layers (M 1 and M 2). M 1.2, L 1 and L 1.2 are considered as high quality reservoir units, because they have high values of porosity and hydrocarbon saturation.